Emerging role for members of the Bcl-2 family in mitochondrial morphogenesis. - MARTIN, SEAMUS (My University, 2009)
Summary Bcl-2 family proteins regulate apoptosis by controlling the release of mitochondrial cytochrome c via the Bax/Bak channel. However, recent studies have also implicated several members of this family in the regulation of mitochondrial fission/fusion dynamics. It has been debated whether the role of Bcl-2 proteins in mitochondrial morphogenesis is functionally distinct from their role in apoptosis, with some arguing that Bax/Bak-induced mitochondrial fission promotes apoptosis-associated cytochrome c release, while others suggest that these functions are separable. Here we review this emerging area and argue for a role for the Bcl-2 family as novel regulators of mitochondrial morphogenesis.
PUBLISHED
Keywords: mitochondrial morphogenesis